Characteristics of First Nations patients who take their own leave from an inner‐city emergency department, 2016–2020. (30th August 2022) - Hutton, Jennie; Gunatillake, Tilini; Barnes, Deborah; Phillips, Georgina; Maplesden, Jacqueline; Chan, Andrew; Shanahan, Prudence; Zordan, Rachel; Sundararajan, Vijaya; Arabena, Kerry; Quigley, Alyssa; Pynor‐Greedy, T'ia; et al.
Abstract: Objective: Using a strength‐based framework, we aimed to describe and compare First Nations patients who completed care in an ED to those who took their own leave. Methods: Routinely collected adult patient data from a metropolitan ED collected over a 5‐year period were analysed. Results: A total of 6446 presentations of First Nations patients occurred from 2016 to 2020, constituting 3% of ED presentations. Of these, 5589 (87%) patients waited to be seen and 857 (13%) took their own leave. Among patients who took their own leave, 624 (73%) left not seen and 233 (27%) left at own risk after starting treatment. Patients who were assigned a triage category of 4–5 were significantly more likely to take their own leave (adjusted odds ratio [OR] 3.17, 95% confidence interval [CI] 2.67–3.77, P  < 0.001). Patients were significantly less likely to take their own leave if they were >60 years (adjusted OR 0.69, 95% CI 1.01–1.36, P  = 0.014) and had private health insurance (adjusted OR 0.61, 95% CI 0.45–0.84, P  < 0.001). Patients were more likely to leave if they were women (adjusted OR 1.17, 95% CI 1.01–1.36, P  = 0.04), had an unknown housing status (adjusted OR 1.76, 95% CI 1.44–2.15, P  < 0.001), were homeless (adjusted OR 1.50, 95% CI 1.22–1.93, P  < 0.001) or had a safety alert (adjusted OR 1.60, 95% CI 1.35–1.90, P  < 0.001). Conclusion: A lower triage category is a strong predictor of First Nations patients taking their own leave. It has been documented that First Nations patients are under‐triaged. One proposed intervention in the metropolitan setting is to introduce practices which expediate the care of First Nations patients. Further qualitative studies with First Nations patients should be undertaken to determine successful approaches to create equitable access to emergency healthcare for this population. Abstract : A comparison of First Nations patients in an inner‐city ED who waited to those who left the ED not seen had a higher triage category. In this setting, a higher triage category could be explored as a way of improving health equity for First Nations patients.